Pragmatic Dimensions of Language Teaching: Theoretical Insights and Classroom Practices - Pandey, Gopal Prasad (Nepalese Linguistics, 2024)
The growing recognition of the role of pragmatic competence in effective communication has led to an increasing interest in its integration within English language teaching. This study explores the integration of pragmatics into English language teaching, focusing on how teachers conceptualize and implement pragmatic instruction within curriculum. The article also highlights the challenges teachers face in integrating pragmatics into the curriculum, such as the lack of explicit guidelines and resources and the difficulty in creating authentic interaction opportunities. Despite these challenges, the article brings out the positive impact of teaching pragmatics on students’ ability to steer social interactions effectively.